Association between health literacy, communication and psychological distress among myelodysplastic syndromes patients. (October 2018) - Ousseine, Youssoufa M.; Butow, Phyllis N.; Fenaux, Pierre; Dring, Rebecca; Festy, Patrick; Restivo, Léa; Vey, Norbert; Mancini, Julien
Highlights: One in three patients (30.7%) had a distress score clinically problematic. Low health literacy was frequent and associated with psychological distress. Difficulties in asking physician's questions were associated with higher distress. Low satisfaction with information about MDS at disclosure also increased distress. Abstract: MDS is a complex and potentially severe disease which can trigger psychological distress. A lack of information received and understood about MDS may also arouse feelings of distress. Low health literacy (HL) might play a role particularly among older patients. Our aim was to assess MDS-related distress and to study the factors associated with it, including medical and non-medical factors such as HL. A self-administered questionnaire was mailed to all members of French and Australian patients' national MDS associations. Data of 280 patients were analysed. A majority of patient (59.5%) reported low functional HL and 50% reported regular difficulties in asking physicians questions. Distress was not modified by gender, awareness of increased risk of developing leukaemia or MDS characteristics. French patients had a higher mean IES score (adjusted β = 5.9, p = 0.004) compared to Australian patients. Poor satisfaction with information provided about MDS, lower functional HL and difficulties in asking physician's questions were also independently associated with distress. MDS-related distress seems more related to HL and communication with physicians than to MDS characteristics. More efforts are needed to improve health literacy, tailor information for MDS patients and support them psychologically in order to improve their emotional well-being.